QatâI Dan ZAnni Dalam Pemikiran Islam (Memahami Teks Dan Konteks Secara Proporsional) - Mufid, Mohammad (Fakultas Adab dan Humaniora UIN Alauddin, 2014)
Term qatâi was at first used in 4th H. It was used in as-Shairafi (w. 330 H.) and al-Jasshash (w.370 H.) era. Both of them are mentioned as the first pioners who popularized term of qatâi. Eventhough, implicitly, as-Syafiâi had mentioned this terms in his book al-Risalah, which had lived long time ago before the era of as-Shairafi and al-Jashshash. The concept of qatâi and zanni were not the final concepts. It is opened to be elaborated. According to Masdar F. Masâudi, the term qatâi is defined as the universal concept and passed through the dimension of time and space (mutlaq). While zanni ia regarded as religious guindance from both al-Quran and Hadis that constitutes the breakdown of the principles of Muhkam texts. The implication of the elaboration consept (qatâi and zanni) has opened the space of ijtihad to the text of qatâi in rank of practice (tatbiq). Along this time, the domain of ijtihad was limited to the text of zanni or it is minimally used when there is no solutions in text of qatâi. Nevertheless, it must be remembered that not all text of qatâi must be comprehended (ijtihad) absolutely. But in other ways, it is limited to qatâiÂ fi baâdi al-ahwal or it pertains qatâI nas Â restrictively.